The Impact of Digital Game-Based Learning on Children's Self-Efficacy and Reading Success - Mahayanti, Ni Wayan Surya; Kusuma, I putu Indra; Ashadi, Ashadi; Rachman, Dzul (VELES Voices of English Language Education Society, 2024)
Numerous studies have indicated that digital games offer a valuable learning experience for young language learners by fostering self-efficacy in English acquisition. Despite this, there remains a dearth of research investigating the impact of digital games on children's self-efficacy and reading achievements. The current study aims to fill this gap by examining (1) the impact of digital games on children's self-efficacy and (2) the effect of digital games on children's reading achievements. An exploratory sequential design was employed, integrating both quantitative and qualitative methods. The study involved 144 young learners in Indonesia who participated in eight treatment sessions using digital games as a learning tool. After these sessions, participants completed a post-test comprising 20 reading items to assess their reading achievements. Observations during the treatment sessions explored the implementation of digital games and their impact on self-efficacy, supplemented by interviews with 15 children to gain deeper insights into their experiences and perceptions. The findings revealed that digital games foster self-efficacy through four mechanisms: mastery experience, vicarious experience, verbal persuasion, and emotional state. These mechanisms are integrated into the game's content, levels, feedback, and challenging activities. The implications suggest that carefully designed digital games can significantly enhance self-efficacy and reading achievements among young learners, offering educators a valuable tool for improving educational outcomes. Future research should explore the long-term effects of digital game-based learning and identify the most effective game features, while also addressing challenges such as equitable access to technology and balancing screen time with other activities.